slurry
By oxidizing the surface of the silicon particles and using a dispersant with a basic functional group, the poor dispersion problem caused by the low affinity of the silicon particles with low polar solvents is solved, and the high dispersion and good adhesion of the active material layer are achieved.
Patent Information
- Application Number
- JP2022004278
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-01-14
AI Technical Summary
When using silicon particles with low polar solvents as the active material, the silicon particles have low affinity with low polar solvents, resulting in poor dispersion of the coating and easy aggregation, affecting the quality of the active material layer.
By oxidizing the surface of the silicon particles, the surface acid points are increased, and the dispersion of the coating is improved by using a dispersant with a basic functional group.
It improves the dispersion of the coating, reduces aggregation phenomenon, and enhances the adhesion of the active material layer, and is suitable for battery manufacturing.
Smart Images

Figure 0007666341000002 
Figure 0007666341000001
Abstract
Description
[Technical field]
[0001] This application relates to slurries. [Background technology]
[0002] In order to form an active material layer of a battery, a slurry containing materials constituting the active material layer may be used. When using a slurry, the active material layer is obtained by applying the slurry to a predetermined substrate and drying it.
[0003] Patent Document 1 discloses a slurry containing a sulfide solid electrolyte and two types of solvents. The same document also describes that the slurry may contain an active material. Patent Document 2 discloses a slurry having a specific surface area of 40 to 300 m2 measured by the BET method. 2 / g, oxygen content (wt%), specific surface area (m 2 Patent Document 3 discloses silicon-based particles having a value of 0.1 or less when divided by the surface area of the silicon-based particles (particle area / g). Patent Document 4 also discloses a slurry containing silicon-based particles. Patent Document 5 discloses a method for producing a slurry containing an oxide active material, a solid electrolyte, a dispersion medium, and at least one of a conductive additive and a binder. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-68673 [Patent Document 2] JP 2017-112057 A [Patent Document 3] JP 2020-177755 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the slurry for forming the active material layer, a low polarity solvent may be used to prevent reaction with the solid electrolyte. On the other hand, when silicon particles are used as the active material, the affinity between the silicon particles and the low polarity solvent is low, so that the dispersibility of the slurry is deteriorated and the particles tend to aggregate. To suppress the aggregation, a dispersant is added to the slurry, but if the surface of the silicon particles is not oxidized, the dispersibility of the slurry is not improved much.
[0006] In view of the above circumstances, a main object of the present disclosure is to provide a slurry that can improve dispersibility. [Means for solving the problem]
[0007] In one embodiment of the present disclosure for solving the above problems, a solvent, silicon particles, a solid electrolyte, and a dispersant are included, the solvent includes a low polarity solvent having a polarity term ΔP of the Hansen solubility parameter of 4 or less, the dispersant includes a first dispersant having a basic functional group, and the silicon particles have a peak at 1600±10 cm in an FT-IR spectrum after pyridine adsorption. -1 Range and 14 43 ±10cm -1 The slurry has a peak in the range of Effect of the Invention
[0008] The slurry of the present disclosure can improve dispersibility. [Brief description of the drawings]
[0009] [Figure 1] FT-IR spectra of silicon particles of Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [slurry] The slurry of the present disclosure contains a solvent, silicon particles, a solid electrolyte, and a dispersant, the solvent contains a low polarity solvent having a polarity term ΔP of the Hansen solubility parameter of 4 or less, the dispersant contains a first dispersant having a basic functional group, and the silicon particles have a peak at 1600±10 cm in an FT-IR spectrum after pyridine adsorption. -1 Range and 14 43 ±10cm -1 It has a peak in the range.
[0011] First, by containing a low polarity solvent with a polarity term ΔP of the Hansen solubility parameter of 4 or less, the reaction between the solvent and the solid content in the slurry, particularly the solid electrolyte, can be suppressed. In addition, the silicon particles have a certain peak in the FT-IR spectrum after pyridine adsorption. This means that there are acid sites on the particle surface. Therefore, the first dispersant having a basic functional group can be efficiently adsorbed to the acid sites on the silicon particle surface, improving the dispersibility of the slurry.
[0012] In addition, an active material layer obtained from a slurry with low dispersibility has a problem of low peel strength, but the slurry of the present disclosure can solve this problem. That is, since the slurry of the present disclosure has high dispersibility, the active material layer obtained from the slurry has a peel strength applicable to battery production.
[0013] The slurries of the present disclosure are further described below.
[0014] <Solvent> The solvent in the present disclosure includes a low polarity solvent having a polarity term ΔP of the Hansen solubility parameter of 4 or less. The solvent may include a solvent other than the low polarity solvent. The solvent other than the low polarity solvent is not particularly limited, and may be a known solvent that is usually used for slurries.
[0015] (low polarity solvent) A low polarity solvent has a polarity term δP of the Hansen solubility parameter of 4 or less. The polarity term δP of the Hansen solubility parameter can be obtained from Hansen Solubility Parameters: A user's handbook, Second Edition. Boca Raton, Fla: CRC Press. (Hansen, Charles (2007)). The unit of solubility is MPa. 0.5 It is.
[0016] Examples of low polarity solvents include tetralin (δP=2), butyl butyrate (δP=2.9), diisobutyl ketone (δP=3.7), mesitylene (δP=0.6), heptane (δP=0), dibutyl ether (δP=3.4), decane (δP=0), toluene (δP=1.4), etc. These may be used alone or in combination.
[0017] The content of the low polarity solvent in the solvent is not particularly limited, but may be, for example, 50% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 100% by weight.
[0018] By containing a low polarity solvent, the reaction between the solvent and the solid content in the slurry, particularly the solid electrolyte, can be suppressed.
[0019] <Silicon particles> The slurry of the present disclosure contains silicon particles. The silicon particles have a peak at 1600±10 cm in the FT-IR spectrum after pyridine adsorption. -1 Range and 14 43 ±10cm -1 This means that there are acid sites on the silicon particle surface. An "acid site" is a site on the surface that functions as an acid (Bronsted acid or Lewis acid). Such acid sites can be expressed by oxidizing the silicon particles and increasing the amount of oxygen on the surface to a certain amount.
[0020] Here, the method of measuring the FT-IR spectrum will be explained. First, the silicon particles are heated to 500°C in an inert atmosphere (for example, an N2 atmosphere). This state is maintained for 30 to 60 minutes. Next, the temperature of the silicon particles is lowered to 100°C, and the atmosphere is reduced pressure. The silicon particles are then exposed to pyridine vapor. Then, the atmosphere is returned to the inert atmosphere, and FT-IR measurement is performed by the diffuse reflectance method. This allows the FT-IR spectrum of the silicon particles after pyridine adsorption to be obtained.
[0021] As described above, silicon particles that can obtain such an FT-IR spectrum need to be oxidized to increase the amount of oxygen. For example, the silicon particles can be oxidized by heating them to 500°C or higher in air or water vapor. The upper limit of the temperature is not particularly limited, but is, for example, 1000°C or lower.
[0022] The oxygen content of the silicon particles is not particularly limited as long as the above FT-IR spectrum can be obtained, but may be, for example, 3 wt % or more, 5 wt % or more, 5.9 wt % or more, 10 wt % or less, 8 wt % or less, or 7 wt % or less.
[0023] The amount of oxygen in silicon particles can be calculated as follows: First, silicon particles are placed in a graphite crucible, heated, and melted, and the amount of CO2 generated is detected using the NDIR method, and the amount of oxygen can be calculated from the results.
[0024] The specific surface area of the silicon particles is not particularly limited, but is, for example, 30 m 2 / g or more, and 2 / g or more, and 60m 2 / g or less, 53m 2 The specific surface area of the silicon particles can be measured by the BET method.
[0025] The ratio of the amount of oxygen to the specific surface area of the silicon particles (oxygen amount / specific surface area) is not particularly limited as long as the above-mentioned FT-IR spectrum can be obtained, but may be, for example, 0.1 or more, 0.111 or more, 0.2 or less, or 0.175 or less.
[0026] The shape of the silicon particles is not particularly limited, and examples thereof include a spherical shape, an oval spherical shape, a columnar shape, and a scale shape. The silicon may be crystalline or amorphous. Furthermore, the silicon particles may be porous.
[0027] The particle size of the silicon particles is not particularly limited, but may be 0.1 μm or more, 1 μm or more, 20 μm or less, 10 μm or less, or 5 μm or less.
[0028] In this specification, the "particle size" can be determined by observing particles with a scanning electron microscope (SEM), counting the long side of a rectangle circumscribing each particle as the diameter, dividing it by the number of particles and averaging it. The number of particles to be measured is at least 10 or more, and preferably 100 or more.
[0029] The content of silicon particles relative to the total solid content in the slurry is not particularly limited, but may be, for example, 30% by weight or more, 50% by weight or more, 80% by weight or less, or 60% by weight or less.
[0030] <Solid electrolyte> The solid electrolyte of the present disclosure is not particularly limited as long as it has Li-ion conductivity and is applicable to all-solid-state lithium-ion batteries. The solid electrolyte may be vitreous (amorphous), crystallized vitreous, or crystalline. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes. The sulfide solid electrolyte is preferred.
[0031] The sulfide solid electrolyte preferably contains Li, M (M is preferably at least one of P, Ge, Si, Sn, B, and Al), and S. The sulfide solid electrolyte may further contain a halogen element. Examples of the halogen element include F, Cl, Br, and I. The amorphous sulfide solid electrolyte may further contain O.
[0032] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In.)
[0033] Examples of oxide solid electrolytes include lithium lanthanum zirconium-containing composite oxide (LLZO), Al-doped LLZO, lithium lanthanum titanium-containing composite oxide (LLTO), Al-doped LLTO, and lithium oxynitride phosphate (LIPON). Examples of nitride solid electrolytes include Li3N and Li3N-LiI-LiOH. Examples of halide solid electrolytes include LiF, LiCl, LiBr, LiI, and LiI-Al2O3.
[0034] The shape of the solid electrolyte is not particularly limited, and examples thereof include a sphere, an oval sphere, a columnar shape, and a scale shape.
[0035] The particle size of the solid electrolyte is not particularly limited, but may be 0.1 μm or more, 1 μm or more, 20 μm or less, 10 μm or less, or 5 μm or less.
[0036] The ratio of the solid electrolyte to the total solid content contained in the slurry is not particularly limited, but may be, for example, 20% by weight or more, 30% by weight or more, 40% by weight or more, 60% by weight or less, or 50% by weight or less.
[0037] <Dispersant> The dispersant in the present disclosure contains a first dispersant having a basic functional group. The dispersant may contain a dispersant other than the first dispersant. The dispersant other than the first dispersant is not particularly limited, and may be a known dispersant that is usually used in slurries. For example, a known surfactant may be mentioned.
[0038] The content of the dispersant relative to the total solid content in the slurry is not particularly limited, but may be, for example, 0.1% by weight or more, 0.5% by weight or more, 0.8% by weight or more, 5% by weight or less, 2% by weight or less, or 1% by weight or less.
[0039] (First dispersant) The first dispersant has a basic functional group. The basic functional group is contained in the solvent-phobic portion of the first dispersant. Examples of the basic functional group contained in the first dispersant include reactive nitrogen-containing functional groups that do not have hydrogen, such as tertiary amino groups, pyridyl groups, and imidazole groups. Examples of the hydrophobic portion include hydrocarbon groups such as alkyl groups. Such a first dispersant is not particularly limited as long as it is soluble in the above-mentioned solvent, and examples thereof include alkylimidazoline. The number of carbon atoms in the alkyl group of the alkylimidazoline is not particularly limited, and is, for example, in the range of 5 to 30.
[0040] By including a first dispersant having a basic functional group in the slurry, the basic functional group of the dispersant can be adsorbed to the acid sites of the silicon particles, thereby improving the dispersibility of the slurry.
[0041] The molecular weight of the first dispersant is not particularly limited, but may be 1000 or less, 800 or less, or 600 or less. The lower limit of the molecular weight of the first dispersant is not particularly limited, but for example, the molecular weight of the first dispersant may be 100 or more, 300 or more, or 400 or more. The molecular weight of the first dispersant can be measured using various NMR (e.g., 1H-NMR, 13C-NMR) or various MS (e.g., ESI-MS).
[0042] The number of carbon atoms in the hydrophobic portion of the first dispersant is not particularly limited, and may be, for example, 5 or more, 10 or more, 30 or less, or 20 or less.
[0043] <Binder> The slurry of the present disclosure may contain a binder as an optional component. The binder is not particularly limited as long as it is applicable to lithium ion batteries. For example, butadiene rubber (BR), butylene rubber (IIR), acrylate butadiene rubber (ABR), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), etc. may be used alone or in combination.
[0044] The binder content relative to the total solid content in the slurry is not particularly limited, but may be, for example, 0.1 weight % or more, 0.3 weight % or more, 0.6 weight % or more, 0.8 weight % or more, 5 weight % or less, 2 weight % or less, 1.1 weight % or less, or 1 weight % or less.
[0045] <Conductive additive> The slurry of the present disclosure may contain a conductive assistant as an optional component. The conductive assistant is not particularly limited as long as it is a binder that can be used in lithium ion batteries. For example, carbon materials such as acetylene black, ketjen black, and vapor grown carbon fiber (VGCF) and metal materials such as nickel, aluminum, and stainless steel can be used.
[0046] The content of the conductive assistant relative to the total solid content in the slurry is not particularly limited, but may be, for example, 1 weight % or more, 2 weight % or more, 4 weight % or more, 10 weight % or less, 8 weight % or less, or 6 weight % or less.
[0047] <Other ingredients> The slurry may contain other components, such as various additives, as necessary.
[0048] <Slurry> The viscosity of the slurry of the present disclosure is not particularly limited, and may be, for example, 10 mPa·s or more, 30 mPa·s or more, 100 mPa·s or less, or 80 mPa·s or less.
[0049] The viscosity of the slurry is measured as follows: The slurry is placed on a cone plate with a diameter of 35 mm and an inclination of 2°, and after rotating the cone plate at a shear rate of 40 / s for 30 seconds, the viscosity of the slurry is measured with a rheometer.
[0050] The particle size of the slurry of the present disclosure is not particularly limited, and may be 1 μm or more, 10 μm or more, 100 μm or more, 500 μm or less, 300 μm or less, or 200 μm or less, and the particle size of the slurry can be measured in accordance with JIS K 5600-2-5:1999.
[0051] The slurry of the present disclosure can be obtained by mixing each component with a solvent. The mixing method is not particularly limited and can be carried out by a known method. For example, the slurry of the present disclosure can be obtained by adding each component to a solvent and mixing them. The mixing method is not particularly limited and may use a blender or may use ultrasonic waves.
[0052] The slurry of the present disclosure is used to form an active material layer for a lithium ion battery, particularly an all-solid-state lithium ion battery. The active material layer may be a positive electrode active material layer or a negative electrode layer, but is preferably a negative electrode active material layer.
[0053] [Method of manufacturing the negative electrode active material layer] The method for producing an anode active material layer according to the present disclosure includes a step of applying the slurry according to the present disclosure to a substrate (application step) and a step of drying the applied slurry (drying step). Since the slurry according to the present disclosure has high dispersibility, the anode active material layer obtained from the slurry has a peel strength applicable to battery production. Therefore, according to the method for producing an anode active material layer according to the present disclosure, an anode active material layer in which the occurrence of slurry application defects is suppressed can be obtained.
[0054] The coating step can be carried out by a known method, such as a doctor blade method, a die coating method, a gravure coating method, a spray coating method, an electrostatic coating method, a bar coating method, etc. The substrate to which the slurry is applied is not particularly limited, and may be a metal foil, a current collector, or a solid electrolyte layer.
[0055] The drying step can be carried out by a known method. For example, the slurry may be heated to a temperature range of 50° C. to 200° C. The atmosphere may be an inert atmosphere or a reduced pressure atmosphere.
[0056] The shape of the obtained negative electrode active material layer is not particularly limited, but it is preferably a sheet shape. The thickness of the negative electrode active material layer is not particularly limited, and may be appropriately set according to the desired battery performance. For example, it is in the range of 0.1 μm to 1 mm.
[0057] [Manufacturing method of all-solid-state batteries] The method for producing an all-solid-state battery according to the present disclosure includes a step of producing an anode active material layer by the method for producing an anode active material layer according to the present disclosure (anode active material layer producing step), a step of producing a cathode active material layer (cathode active material layer producing step), a step of producing a solid electrolyte layer (solid electrolyte layer producing step), and a step of laminating the anode active material layer, the solid electrolyte layer, and the cathode active material layer in this order (lamination step). According to the method for producing an all-solid-state battery according to the present disclosure, an all-solid-state battery including an anode active material layer in which the occurrence of slurry coating defects is suppressed can be obtained.
[0058] <Negative electrode active material layer preparation process> The negative electrode active material layer preparation step is carried out by the method for producing a negative electrode active material layer of the present disclosure. In the negative electrode active material preparation step, a negative electrode current collector may be used as a substrate to which the slurry is applied. This allows the negative electrode to be prepared.
[0059] The material of the negative electrode current collector can be appropriately selected from known materials according to the purpose. For example, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. can be mentioned. The thickness of the negative electrode current collector is not particularly limited and may be appropriately set according to the desired battery performance. For example, it is in the range of 0.1 μm to 1 mm.
[0060] <Positive electrode active material layer preparation process> The positive electrode active material layer preparation step can be carried out by a known method. For example, the materials constituting the positive electrode active material layer are mixed in a dry state and pressed to obtain the positive electrode active material layer. Alternatively, the materials constituting the positive electrode active material layer are dispersed in a solvent to form a slurry, and the obtained slurry is applied to a substrate and dried to obtain the positive electrode active material layer. A positive electrode current collector may be used as the substrate. This allows the positive electrode to be prepared. The positive electrode current collector and the positive electrode active material layer will be described below.
[0061] The material of the positive electrode current collector is not particularly limited, and can be appropriately selected from known materials according to the purpose. For example, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. can be mentioned. The thickness of the positive electrode current collector is not particularly limited, and can be appropriately set according to the desired battery performance. For example, it is in the range of 0.1 μm to 1 mm.
[0062] The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material can be appropriately selected from known positive electrode active materials used in all-solid-state lithium ion batteries. Examples include lithium cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), and lithium manganese oxide. The particle size of the positive electrode active material is not particularly limited, but is, for example, in the range of 1 μm to 100 μm. The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is, for example, in the range of 50% by weight to 99% by weight. In addition, the surface of the positive electrode active material may be covered with an oxide layer such as a lithium niobate layer, a lithium titanate layer, or a lithium phosphate layer.
[0063] The positive electrode active material layer may optionally include a solid electrolyte. The solid electrolyte may be appropriately selected from known solid electrolytes used in all-solid-state lithium ion batteries. For example, the solid electrolyte may be contained in the above-mentioned slurry. The content of the solid electrolyte in the positive electrode active material layer is not particularly limited, but is, for example, in the range of 1% by weight to 50% by weight.
[0064] The positive electrode active material layer may optionally include a conductive assistant. The conductive assistant can be appropriately selected from known conductive assistants used in all-solid-state lithium ion batteries. For example, the conductive assistant can be included in the above-mentioned slurry. The content of the conductive assistant in the positive electrode active material layer is not particularly limited, but is, for example, in the range of 0.1% by weight to 10% by weight.
[0065] The positive electrode active material layer may optionally include a binder. The binder may be appropriately selected from known binders used in all-solid-state lithium ion batteries. For example, the binder may be one that can be contained in the above-mentioned slurry. The content of the binder in the positive electrode active material layer is not particularly limited, but is, for example, in the range of 0.1% by weight to 10% by weight.
[0066] The shape of the positive electrode active material layer is not particularly limited, but is preferably a sheet shape. The thickness of the positive electrode active material layer is not particularly limited, and may be appropriately set according to the desired battery performance. For example, it is in the range of 0.1 μm to 1 mm.
[0067] <Solid electrolyte layer production process> The solid electrolyte layer preparation step can be carried out by a known method. For example, the materials constituting the solid electrolyte layer are mixed in a dry state and pressed to obtain the solid electrolyte layer. Alternatively, the materials constituting the solid electrolyte layer are dispersed in a solvent to form a slurry, and the obtained slurry is applied to a substrate and dried to obtain the solid electrolyte layer. The solid electrolyte layer will be described below.
[0068] The solid electrolyte layer contains at least a solid electrolyte. The solid electrolyte can be appropriately selected from known solid electrolytes used in all-solid-state lithium ion batteries. For example, the solid electrolyte can be contained in the above-mentioned slurry. The content of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, in the range of 50% by weight to 99% by weight.
[0069] The solid electrolyte layer may also contain a binder. The binder may be appropriately selected from known binders used in all-solid-state lithium ion batteries. For example, the binder may be one that can be contained in the above-mentioned slurry. The content of the binder in the solid electrolyte layer is not particularly limited, but is, for example, in the range of 0.1% by weight to 10% by weight.
[0070] The shape of the solid electrolyte layer is not particularly limited, but is preferably a sheet. The thickness of the solid electrolyte layer is not particularly limited and may be appropriately set according to the desired battery performance. For example, it is in the range of 0.1 μm to 1 mm.
[0071] <Lamination process> The lamination step is a step of laminating the negative electrode active material layer, the solid electrolyte layer, and the positive electrode active material layer in this order. After laminating these layers, the laminate may be pressed. The pressing method is not particularly limited, but examples thereof include roll pressing and flat plate pressing. The linear pressure applied during roll pressing may be, for example, 1 t / cm or more and 10 t / cm or less. The surface pressure applied during flat plate pressing may be, for example, 800 MPa or more and 3000 MPa or less.
[0072] After the lamination step, the negative electrode current collector may be disposed on the surface of the negative electrode active material layer, and the positive electrode current collector may be disposed on the surface of the positive electrode active material layer.
[0073] When a negative electrode current collector and a positive electrode current collector are used as the substrate in the negative electrode active material layer forming step and the positive electrode active material layer forming step, the negative electrode, solid electrolyte layer, and positive electrode may be laminated in this order in the lamination step.
[0074] The all-solid-state battery obtained by the manufacturing method of the all-solid-state battery of the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a stacked battery connected in parallel) or a bipolar stacked battery (a stacked battery connected in series). The shape of the all-solid-state battery may be, for example, a coin type, a laminated type, a cylindrical type, or a square type. EXAMPLES
[0075] The slurries of the present disclosure will be further illustrated by examples.
[0076] <Preparation of slurry> Using the materials and contents described in Table 1, slurries of Examples 1 to 2 and Comparative Examples 1 to 2 were prepared. First, the materials were put into a 5 mL container at once so that the total volume became 3.5 mL. Next, while cooling the obtained mixture to 10 °C, ultrasonic waves with an amplitude of 40 μm and a frequency of 20 kHz were irradiated for 40 minutes using a φ3.5 mm ultrasonic horn to disperse. Thus, slurries of Examples 1 to 2 and Comparative Examples 1 to 2 were prepared.
[0077] Here, the solid electrolyte in Table 1 is a sulfide solid electrolyte. The dispersant is alkylimidazoline (molecular weight: about 500). The solvent is diisobutyl ketone (DIBK).
[0078] <FT-IR Measurement> Using an FT-IR device varian7000, the FT-IR spectra of the silicon particles of Example 1 and Comparative Example 1 were measured as follows. First, the silicon particles were heated to 500 °C in an N2 atmosphere. This state was maintained for 30 minutes or more. Next, the temperature of the silicon particles was lowered to 100 °C to create a reduced-pressure atmosphere. Subsequently, the silicon particles were exposed to pyridine vapor. Then, it was returned to an N2 atmosphere again, and FT-IR measurement was performed by the diffuse reflection method. Thus, the FT-IR spectrum of the silicon particles after pyridine adsorption was obtained.
[0079] The FT-IR spectra of Example 1 and Comparative Example 1 are shown in FIG. 1. As shown in FIG. 1, no peaks could be confirmed near 1600 cm -1 and near 1400 cm -1 . In contrast, sharp peaks could be confirmed near 1600 cm -1 and near 14 43 cm -1 for Example 1. Therefore, it was confirmed that acid sites exist on the surface of the silicon particles of Example 1.
[0080] <Specific Surface Area Measurement> Using the BET method, the specific surface areas of the silicon particles of Examples 1 to 2 and Comparative Examples 1 to 2 were measured. The results are shown in Table 1.
[0081] <Oxygen measurement> Using an oxygen content analyzer EMGA920, the oxygen content of silicon particles in Examples 1-2 and Comparative Examples 1-2 was measured as follows. The silicon particles were placed in a graphite crucible and heated to melt the silicon particles. The amount of CO2 generated during this process was detected by NDIR. The amount of oxygen was calculated from the results obtained. The results are shown in Table 1. Table 1 also shows the ratio of the amount of oxygen to the specific surface area of the silicon particles.
[0082] <Viscosity measurement> The viscosity of Examples 1-2 and Comparative Examples 1-2 was measured using a viscosity measuring device MCR302 as follows. The slurry was placed on a cone plate with a diameter of 35 mm and an inclination of 2°, and the cone plate was rotated at a shear rate of 40 / s for 30 seconds, after which the viscosity of the slurry was measured. The results are shown in Table 1.
[0083] In Table 1, the points marked with "-" indicate that the aggregates had settled and could not be measured.
[0084] <Particle size measurement> The particle sizes of the slurries of Examples 1 and 2 and Comparative Examples 1 and 2 were measured. The particle size measurement method was carried out in accordance with JIS K 5600-2-5:1999. The results are shown in Table 1.
[0085] In Table 1, the points marked with "-" indicate that the aggregates had settled and could not be measured.
[0086] <Dispersibility evaluation> The state of the slurry was evaluated visually, and the absence of agglomerates was evaluated as "good", and the presence of agglomerates was evaluated as "bad". In addition, when agglomerates were present, the state of the agglomerates was evaluated. The results are shown in Table 1.
[0087] [Table 1]
[0088] <Result> From Table 1, it can be seen that the dispersion evaluation results were good in Examples 1 and 2. On the other hand, the dispersion evaluation results for Comparative Examples 1 and 2 were "x".
[0089] In Comparative Example 1, the amount of oxygen in the silicon particles was small, and the ratio of the amount of oxygen to the specific surface area was also small. Therefore, the silicon particles did not have acid sites (FIG. 1), and the dispersant was not properly adsorbed, which is thought to have caused the low dispersibility of the slurry. In Comparative Example 2, the same silicon particles as in Example 1 were used, but the dispersant was not included, which is thought to have caused the low dispersibility of the slurry.
Claims
[Claim 1] The composition contains a solvent, silicon particles, a solid electrolyte, and a dispersant, The solvent includes a low polarity solvent having a polarity term δP of the Hansen solubility parameter of 4 or less; The dispersant contains a first dispersant having a basic functional group, the first dispersant is an alkyl imidazoline; The ratio of the amount of oxygen to the specific surface area of the silicon particles is 0.1 or more; The silicon particles have peaks in the range of 1600±10 cm −1 and 1443±10 cm −1 in the FT-IR spectrum after pyridine adsorption. slurry.
Citation Information
Patent Citations
All-solid type secondary battery, composition for electrode active material layer, electrode sheet for all-solid type secondary battery, and manufacturing methods for all-solid type secondary battery and electrode sheet for all-solid type secondary battery
JP2016212990A
Silicon-based particle, lithium ion secondary battery negative electrode active material including the same, and manufacturing methods thereof
JP2017112057A
All-solid battery
JP2020053300A
Negative electrode layer
JP2020119811A
Method for manufacturing slurry, method for manufacturing active material layer and method for manufacturing all-solid battery
JP2020177755A